Evaluation of the registry DIALYREG for the assessment of continuous renal replacement techniques in the critically ill patient - Gonzalez Fernandez, M; Quiles Trasobares, N; Barea Mendoza, JA; Molina Collado, Zaira; Arias Verdú, Dolores; Barrueco Francioni, Jesus Emilio; Seller Pérez, Gemma Luisa; Herrera-Gutiérrez, Manuel Enrique; Sánchez Izquierdo Riera, José Ángel (Nature, 2023)
Continuous renal replacement techniques (CRRT) can induce complications and monitoring is crucial to ensure patient safety. We designed a prospective multicenter observational and descriptive study using the DIALYREG registry, an online database located on a REDCap web-based platform that allows real-time data analysis. Our main objective was to identify CRRT-related complications in our intensive care units (ICUs) and implement security measures accordingly. From January 2019 to December 2020, we included 323 patients with admission diagnoses of medical illness (54%), sepsis (24%), postoperative care (20%), and trauma (2%). CRRT indications were homeostasis (42%), oliguria (26%), fluid overload (15%), and hemodynamic optimization (13%). The median initial therapy dose was 30 ml/kg/h (IQR 25-40), and dynamic adjustment was performed in 61% of the treatments. Sets were anticoagulated with heparin (40%), citrate (38%) or no anticoagulation (22%). Citrate anticoagulation had several advantages: more frequent dynamic CRRT dose adjustment (77% vs. 58% with heparin and 56% without anticoagulation, p < 0.05), longer duration of set (median of 55 h, IQR 24-72 vs. 23 h, IQR 12-48 with heparin and 12 h, IQR 12-31 without anticoagulation, p < 0.05), less clotting of the set (26% vs. 46.7% with heparin, p < 0.05), and lower incidence of hypophosphatemia (1% citrate vs. 6% with heparin and 5% without anticoagulation). It was also safe and effective in subgroup analysis of patients with liver disease or sepsis. The main global complications were hypothermia (16%), hypophosphatemia (13%) and metabolic acidosis (10%). Weaning of the therapy was achieved through early discontinuation (56%), nocturnal therapy transition (26%) and progressive SLED (18%). 52% of the patients were discharged from the hospital, while 43% died in the ICU and 5% died during hospitalization. We can conclude that the DIALYREG registry is a feasible tool for real-time control of CRRT in our ICU.
Keywords: Dialyreg - Bases de datos; Acute Kidney Injury; Citrate; Critical Illness